Back Cover: Dynamics of Novel Photoactive AgCl Microstars and Their Environmental Applications (ChemNanoMat 1/2017). Issue 1 (23rd December 2016) - Simmchen, Juliane; Baeza, Alejandro; Miguel‐Lopez, Albert; Stanton, Morgan M.; Vallet‐Regi, Maria; Ruiz‐Molina, Daniel; Sánchez, Samuel
Abstract : Silver chloride has the inherent ability to transform light energy into surface chemical reactions. Here, this property is used to achieve self‐propulsion of octapod‐shaped AgCl particles. The top view SEM image shows several of the particles and the inset shows a schematic illustrating the propulsion. For the characterization of motion, the dynamics of single particles are analyzed, and then applications of light‐driven particles are presented. More information can be found in the Full Paper by J. Simmchen et al. onpage 65 in Issue 1, 2017 (DOI:10.1002/cnma.201600300 ).